Small dimension–Big impact! Nanoparticle-enhanced non-invasive and intravascular molecular imaging of atherosclerosis in vivo - Lenz, Tobias; Nicol, Philipp; Castellanos, Maria Isabel; Engel, Leif Christopher; Lahmann, Anna Lena; Alexiou, Christoph; Joner, Michael (Molecules, 2020)
Extensive translational research has provided considerable progress regarding the understanding of atherosclerosis pathophysiology over the last decades. In contrast, implementation of molecular in vivo imaging remains highly limited. In that context, nanoparticles represent a useful tool. Their variable shape and composition assure biocompatibility and stability within the environment of intended use, while the possibility of conjugating different ligands as well as contrast dyes enable targeting of moieties of interest on a molecular level and visualization throughout various imaging modalities. These characteristics have been exploited by a number of preclinical research approaches aimed at advancing understanding of vascular atherosclerotic disease, in order to improve identification of high-risk lesions prior to oftentimes fatal thromboembolic events. Furthermore, the combination of these targeted nanoparticles with therapeutic agents offers the potential of site-targeted drug delivery with minimized systemic secondary effects. This review gives an overview of different groups of targeted nanoparticles, designed for in vivo molecular imaging of atherosclerosis as well as an outlook on potential combined diagnostic and therapeutic applications.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Atherosclerosis; Molecular imaging; Nanoparticles